Tinjauan Yuridis Euthanasia Dalam Hukum Pidana (Studi Perbandingan Hukum Pidana di Beberapa Negara) - Mayasari, Cicik Panca (JURNAL PROPERTY RIGHTS, 2014)
Nowadays, social culture has changed in the society. Most of them dominated with the new knowledge and new innovations of modern technology. One of them is medicine that has dominated of new innovations and modern technology. Through the progress of medical technology modern, then the diagnosis of disease could be done more effective in medicinal treatment. Even though, the progress of health has reduce and lost the illness even the medical patient have a hold life by the ârespiratorâ, but sometimes the medical patient cannot be save. This happen will be discomposed of the family by the medical patient, and then they chose the way is doing by euthanasia practical. From many sources there are many kinds of euthanasia practical. Nevertheless, all of them are part of humanâs right. And then euthanasia have contravene of morality, social, law and religion.Â Â Â Â Â Â Â Â Â Â Â  The approximation method will be use is approximation of laws of KUHP and comparative approximation that compare between the rules of laws from Indonesia and Holland. About the rule of euthanasia from America and Belgium.Â Â Â Â Â Â Â Â Â Â Â  Actually, the morality of passive euthanasia it could receive by society in Indonesia. So that the doctor is cannot be a killer which is continuing ever after. Though, the asking of doing the euthanasia active will become fidgety by the doctor. If we refer to the law especially the criminal of law, then euthanasia is part of criminal that killing of humanâs life based on criminal of law no 334 KUHP. Based on the history, this section never getting of the euthanasiaâs doer so that is not effective. The reformism development of law especially in criminal law, so that the number 344 KUHP need more observation that can be useful for the social development. The country has legality of the euthanasia have a specific rule and submission procedure of euthanasia that is much closed with the stages.Â Â Â Â Â Â Â Â Â Â Â  The government should be specific organize about the problem of euthanasia then there is no conflict for one to another. Necessary to presence the laws that its can arrange the problem of euthanasia.